Digital Patriarchy: How Indonesian Islamic Preachers Construct Gender Asymmetry through YouTube Fatwas - Falah, Mohammad Bachrul; Riyanta, Riyanta (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
Social media has emerged as a new platform for religious figures to disseminate fatwas (Islamic legal opinions). These platforms undoubtedly facilitate public access to pragmatic answers regarding Islamic legal issues. However, the credibility of fatwas issued on social media is frequently contested, particularly concerning gender bias. This study examines religious figures’ fatwas on YouTube about spousal relations through the lens of feminist theory. Employing a qualitative empirical approach, the research utilizes netnography as its data collection method. The findings reveal that most religious figures’ fatwas on position the wife in a state of economic dependence on her husband, while relegating her to domestic roles with obligations centered on fulfilling spousal domestic needs, particularly sexual demands. Such narratives starkly contradict principles of gender equality and perpetuate bias by potentially disregarding wives’ sexual agency. These fatwas stem from conservative interpretations of Q.S 4:34 by religious figures. [Media sosial muncul sebagai platform baru bagi tokoh agama untuk menyebarkan fatwa (pendapat hukum Islam). Platform ini memudahkan akses publik terhadap jawaban-jawaban praktis terkait persoalan hukum Islam. Namun, kredibilitas fatwa yang dikeluarkan di media sosial sering kali diperdebatkan, terutama terkait dengan bias gender. Penelitian ini mengkaji fatwa para tokoh agama di YouTube mengenai relasi suami-istri melalui perspektif teori feminis. Dengan menggunakan pendekatan kualitatif, dalam beberapa hal penelitian ini menerapkan bagian dari kerja netnography sebagai teknik pengumpulan data. Hasil penelitian menunjukkan bahwa sebagian besar fatwa yang disampaikan oleh para tokoh agama menempatkan istri dalam posisi ketergantungan ekonomi terhadap suaminya, sekaligus membatasi perannya pada ranah domestik dengan kewajiban yang berfokus pada pemenuhan kebutuhan rumah tangga suami, khususnya kebutuhan seksual. Narasi semacam ini secara jelas bertentangan dengan prinsip kesetaraan gender dan memperkuat bias dengan berpotensi mengabaikan agensi seksual istri. Fatwa-fatwa tersebut berakar pada tafsir konservatif terhadap Q.S. 4:34 oleh para tokoh agama.]